2018
DOI: 10.1177/1461444818804773
|View full text |Cite
|
Sign up to set email alerts
|

Dating gone mobile: Demographic and personality-based correlates of using smartphone-based dating applications among emerging adults

Abstract: Mobile dating is more common with an increasing number of smartphone applications coming to market that aim to facilitate dating. In the current study, we investigated how dating app use and motivations related to demographic identity variables (i.e. gender and sexual orientation) and personality-based variables among young adults. Nearly half of the sample used dating apps regularly, with Tinder being the most popular. Non-users were more likely to be heterosexual, high in dating anxiety, and low in sexual pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
115
3
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(130 citation statements)
references
References 53 publications
(112 reference statements)
5
115
3
7
Order By: Relevance
“…Therefore, it is not surprising that Tinder and similar dating apps started to receive quite some research attention in recent years. Previous studies have investigated the use of online dating platforms from various perspectives, including the users' demographic background, personality traits, motives of use, and self-presentation strategies (e.g., Sumter & Vandenbosch, 2019;Timmermans & De Caluwé, 2017a, 2017b. However, despite convincing calls for action by both media and psychology scholars (e.g., Lomanowska & Guitton, 2016;Orosz et al, 2016;Strubel & Petrie, 2017), little research has focused on Tinder users' well-being.…”
mentioning
confidence: 99%
“…Therefore, it is not surprising that Tinder and similar dating apps started to receive quite some research attention in recent years. Previous studies have investigated the use of online dating platforms from various perspectives, including the users' demographic background, personality traits, motives of use, and self-presentation strategies (e.g., Sumter & Vandenbosch, 2019;Timmermans & De Caluwé, 2017a, 2017b. However, despite convincing calls for action by both media and psychology scholars (e.g., Lomanowska & Guitton, 2016;Orosz et al, 2016;Strubel & Petrie, 2017), little research has focused on Tinder users' well-being.…”
mentioning
confidence: 99%
“…However, in our sample, exposure to multiple sexual partners was reported three times more by male participants. Some studies have reported the influence of gender on sexual practice, showing that men tend to seek multiple sexual partners using apps and websites [ 6 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most apps are free, and users can chat with a large number of people through location-based algorithms using a Global Positioning System (GPS). Interpersonal encounters arranged through apps vary from social networking to finding sexual partners [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stinson (2010) and Sevi et al (2017) explores the factors associated to having casual sex, or, having "friends with benefits"; existing scholarly research has to date explored the use of the dating app Tinder to understand user's motivations and perspectives (Timmermans & De Caluwé, 2017). Additional research has focused on the issues surrounding body image (Strubel & Petrie, 2017), social anxiety and the affordability of socially connecting with others (Steven & Morris, 2007), personality-based usage, and motivations of specific factors such as gender, and sexual orientation (Sumter & Vandenbosch, 2019). In heterosexual matches, the woman has 24 hr to make the first move and the man has 24 hr to respond.…”
Section: Mobile Dating Appsmentioning
confidence: 99%